Does natural gas consumption mitigate CO2 emissions: Testing the environmental Kuznets curve hypothesis for 14 Asia-Pacific countries. (October 2018) - Dong, Kangyin; Sun, Renjin; Li, Hui; Liao, Hua
Abstract: This study aims to investigate the nexus of per capita carbon dioxide (CO2 ) emissions, per capita gross domestic product (GDP), and per capita natural gas consumption by examining the validity of the environmental Kuznets curve (EKC) hypothesis and analyzing the effectiveness of natural gas consumption for a panel of 14 Asia-Pacific countries for 1970–2016. To do so, a Granger causality framework covering panel unit root, cointegration, estimation, and causality tests allowing for cross-sectional dependence is employed. The main findings are: (i) The augmented mean group (AMG) estimates provide strong evidence in favor of the EKC hypothesis as the EKC holds in 13 of the 14 countries; the EKC exists independent of the individual country's per capita GDP; (ii) the turning points (TPs) lie between 1937.23 (Bangladesh) and 58, 235.90 (Australia), while the turning years (TYs) are estimated to stay between 2019 (Australia) and 2048 (Bangladesh); per capita GDP positively and negatively affects the TPs and TYs, respectively; (iii) natural gas consumption has a significantly negative effect on CO2 emissions; the significantly negative effect of natural gas consumption on CO2 emissions is also independent of per capita GDP but, conversely, may be affected by the proportion of natural gas in the primary energy mix; and (iv) bidirectional causality runs between natural gas consumption and CO2 emissions in both the short run and long run. Important policy implications are highlighted for Asia-Pacific countries' policymakers with respect to halting global warming and promoting growth in the natural gas industry. Highlights: This study investigates the emission-growth-energy nexus in 14 Asia-Pacific countries for 1970–2016. Recent panel approaches allowing for cross-sectional dependence are employed. Results strongly validate the EKC hypothesis for CO2 emissions. Natural gas consumption can mitigate CO2 emissions. Short- and long-run bidirectional causal links between natural gas consumption and CO2 emissions exist.